2017
DOI: 10.5455/medarh.2017.71.308-311
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Aloe Vera on TNF-a Levels, the Percentage of Nk Cells and Th 17 Cells in Rat That Received Izoniazid and Rifampycin

Abstract: Background:The present study was undertaken to investigate the hepatoprotective effect of Aloe vera against side effect of antituberculosis drug.Material and methods:Twenty-five rats will be divided into five groups, namely the control group (without any treatment), the group of rats treated with anti-tuberculosis drugs, and a group of rats were treated antituberculosis drugs and got Aloe vera extract at a dose of 40; 80; and 120 mg/kg body weight. Antituberculosis drugs are isoniazid and rifampicin a dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The liver damage was identified from the liver inflammation, necrosis, and steatosis [4]. A similar finding was reported by Mawarti et al (2017). The study revealed an increased level of TNF-α and IL-6 in the rats' liver after administration of INH and RIF.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The liver damage was identified from the liver inflammation, necrosis, and steatosis [4]. A similar finding was reported by Mawarti et al (2017). The study revealed an increased level of TNF-α and IL-6 in the rats' liver after administration of INH and RIF.…”
Section: Discussionsupporting
confidence: 82%
“…Those in vivo studies had confirmed the toxic effect of antituberculosis drugs on the liver, one of which was an enhanced level of pro-inflammatory cytokines such as TNF-α and IL-6. However, the dosage and the component of antituberculosis regimen, as well as the duration of antituberculosis administration, varied among studies [3], [9], [10], [11], [12]. This research also revealed that INH-RIF administration would lead to liver damage on rats, which was identified from the histopathology examination.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…As a result, the liver cells become more susceptible to apoptotic effects of TNF-α and IFN-γ. These effects can be inhibited by inhibitors of apoptosis proteins (IAPs) or Bcl-2 47 . IL-4 is one cytokine that has been linked to the development of immune-mediated DILI as well as its associated antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the optimum effect in IL-12 secretion was 10 mg/kg with mitogen stimulating but in doses of 50 and 100 mg/kg were the optimum points to produce IL-12 cytokine from macrophage. [16]. In another study, Habeeb et al reported that Aloe vera can suppress TNF-α production and modulate inflammatory responses in bacterial infection [17].…”
Section: Discussionmentioning
confidence: 99%